ITIL V4 Implementation for Improving IT Service Quality: A Case Study at XYZ Company - Dani Putra Rachman Akbar; Nilo Legowo (Politeknik Siber Cerdika Internasional, 2026)
Background: Information systems are core components impacting the continuity of organizational leadership and management, especially for organizations whose daily operational activities rely heavily on technology. The performance of IT services needs to be measured in a systematic and reliable way so that these services can always meet the expectations of users. Objectives: This study aims to measure and improve the effectiveness and process improvement of IT Service Desk and IT End User Computing units through the implementation of ITIL 4. Methods: Qualitative case study using the DMAIC (Define, Measure, Analyze, Improve, Control) framework. The data collection methods employed for this phase consisted of primary sources (structured interviews with 100 respondents at 4 different divisions as well as direct field observations) and secondary sources (operational reports from ServiceNow ticketing system, service delivery, roles and assessment tools spanning January–December 2023). The methodology functions as a never-ending improvement loop. ITIL 4 practices are adopted in parallel to strengthen service management maturity and operational efficiency. Results: We present three frameworks that together provide a structured approach to designing, identifying gaps in, and improving aspects of service delivery processes. Findings show that ITIL-led initiatives have a positive impact on resolving Incidents faster, moving IT Service Desk maturity from Level 4 to Level 5 at